2022
DOI: 10.2147/ccid.s357810
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Blood Cell Secretome (BCS) Counteracts Skin Aging: Multi-Center Prospective Regenerative Aesthetic Medicine Study Using Exokine®

Abstract: Background:The "Inflammation Theory of Ageing" identifies pro-inflammatory cytokines and oxidative damage as one cause of cellular and mitochondrial deterioration and aging. Cell-free blood cell secretome (BCS) also known as autologous conditioned serum (ACS) has shown anti-inflammatory and regenerative mode of action in musculoskeletal disorders and radicular compression. Aim: To confirm that BCS can improve signs of skin aging from a previous study in a multi-center setting. Methods: Prospective, one-armed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Compared to SC preparations, SC secretome has several advantages, including ease of manufacture, freeze-drying, packaging, and easier transportation ( Xia et al, 2019 ). In addition, the SC secretome has shown potential to counteract facial aging ( Kerscher et al, 2022 ). PT Kimia Farma Tbk (Jakarta, Indonesia; https://www.kimiafarma.co.id/ ) develops an h D-MSC secretome preparation for facial aging.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to SC preparations, SC secretome has several advantages, including ease of manufacture, freeze-drying, packaging, and easier transportation ( Xia et al, 2019 ). In addition, the SC secretome has shown potential to counteract facial aging ( Kerscher et al, 2022 ). PT Kimia Farma Tbk (Jakarta, Indonesia; https://www.kimiafarma.co.id/ ) develops an h D-MSC secretome preparation for facial aging.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical data have suggested that BCS may also offer potential benefits in combating skin aging. Clinical study conducted by Kerscher et al, in 2021, demonstrated that BCS significantly improves skin firmness and hydration after 12 and 24 weeks of use (Kerscher et al, 2021). In addition to the clinical evidence, in vitro experiments conducted on a well-described skin model further support BCS as a beneficial agent for cell division and overall skin quality (Schmitt et al, 2018).…”
Section: Cell-free Therapymentioning
confidence: 99%
“…BCS involves enriching blood serum with bioactive secretions from blood cells, essential for clotting, infection prevention, wound healing, and tissue restoration. These techniques typically entail the preparation and local application of these substances to enhance skin rejuvenation and healing (Kerscher et al, 2022). BCS has demonstrated effectiveness in treating musculoskeletal disorders.…”
Section: Cell-free Therapymentioning
confidence: 99%
See 2 more Smart Citations